(untitled) (European Journal of Language and Literature, 2017)
Through this research we are going to analyze the learning skills, thus competencies needed by students during the learning process and acquisition of a foreign language of specific purpose. The purpose of such a research is not only to identify difficulties they encounter during the learning process but also to introduce special techniques and strategies for a specific teaching process aiming at enhancement of communicative competence as primary goal of teaching/learning process. The applied method is that of survey (40 hours of study time). We have put in evidence and made remarks of the most common difficulties for students based on an assessment table. In the second part of the research, based on survey results, there are presented teaching suggestions and techniques which help students to overcome obstacles and guide them to acquire learning skills to the final end of acquisition of specialized communication competence. Besides the theoretical part there are presented practical aspects of didactic activities related to the analyzed skills.